ダイ13ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1972 - 藤沢, 格; フジサワ, イタル; 福谷, 博; フクタニ, ヒロシ; 白土, 武久; シラツチ, タケヒサ; FUJISAWA, Itaru; FUKUTANI, Hiroshi; SHIRATUCHI, Takehisa (国立極地研究所, 1974)
P(論文) This paper describes the results of meteorological surface and aerological observations at Syowa Station from February 1, 1972 to February 10, 1973. The main subjects of observations, the method, and the equipments are the same as the previous year. Observed results (surface observation at 00, 06, 09, 12, 15, 18 GMT and aerological observation at 00 GMT) were sent to World Meteorological Centre in Melbourne via Mawson Station based on the WMO code, and were recorded according to the WMO regulations. Meteorological characters observed this year are as follows: 1) Temperature in the first half of this year was a little lower than the average but was unusualy high in August and September. 2) Snow accumulation in August and September was larger than in normal years, 3) The sunshine duration in the latter half was extremely shorter than in normal years, arid consequently, the thawing of snow was very slow. 4) Sudden warming in the lowci stratosphere was observed clearly since October 8. For instance, the isotherm of -50℃ was found to shift downward periodically, with a period of 11 or 12 days. 5) A rainbow was observed on the early moring of December 17. 1972. This was the first recoid ever since Syowa Station was opened. Moreover, we carried out observations of drifting snow, total amount of ozone, amount of evaporation, katabatic wind as well as atmospheric ozone, electricity and long wave radiation using a specially desinged radiosonde. departmental bulletin paper